The new revolution in the cotton economy mechanization and its consequences - Street, James Harry 1915-1988 (University of North Carolina Press, 1957)
This is the belt and most comprehensivc presentation of the evolution and recent revolution in the cotton economy and analysis of the economic and social factors involved that has appered in print .. Part I of this book gives a good brief account of the early days of cotton in America and covers the era of expansion following Invention of cotton gin and the introduction of the Mexican variety of cotton. There is an excellent description of adjustments made following the Civil War, particularly the rise of the crop-lien, time-credit, supply-merchant system, and the westward movement of cotton production.
Bibliographie: Seite 253-283
Keywords: Algodão; Economia agrícola; Mecanização agrícola; Cotton growing -- United States; Farm mechanization; Baumwollindustrie; Baumwollanbau; Baumwollwirtschaft; USA